Log in to add a comment

## Answers

**( please read the following steps continuously I just separated so that it would be easy for you to understand the terms )**

consider a body is having initial velocity that is represented as "u"

that body is in uniform acceleration "a"

after some time "t"

the body final velocity "v"

**considering the definition of the acceleration :**

acceleration = change in velocity

--------------------------

time

acceleration = final velocity - initial velocity

------------------------------------

time

=> a = v-u

-----

t

=> (v-u) = at

=> v = u + at

**hence the equation is derived.**

**hope so it is clear and understandable.**